2020
DOI: 10.1080/14693062.2020.1831432
|View full text |Cite
|
Sign up to set email alerts
|

Carbon pricing and COVID-19

Abstract: A question arising from the COVID-19 crisis is whether the merits of cases for climate policies have been affected. This article focuses on carbon pricing, in the form of either carbon taxes or emissions trading. It discusses the extent to which relative costs and benefits of introducing carbon pricing may have changed in the context of COVID-19, during both the crisis and the recovery period to follow. In several ways, the case for introducing a carbon price is stronger during the COVID-19 crisis than under n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…This mechanism is referred to as the carbon taxation, which is an economic signal that mandates emitters to incur monetary loss for adopting non-green practices and at the same time push them to adopt eco-friendly products and services. Apart from its deterrence motive, the tax revenues collected from such initiative are channelized to promote energy innovation (to reduce the carbon footprint in future), and in some cases, such revenue streams are directed towards building social safety nets, which is especially attracting attention of the policymakers in the developing markets (Mintz-Woo et al, 2020). However, it is often observed that the burden of carbon taxation is relatively less in comparison to investment in eco-friendly designs and practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is referred to as the carbon taxation, which is an economic signal that mandates emitters to incur monetary loss for adopting non-green practices and at the same time push them to adopt eco-friendly products and services. Apart from its deterrence motive, the tax revenues collected from such initiative are channelized to promote energy innovation (to reduce the carbon footprint in future), and in some cases, such revenue streams are directed towards building social safety nets, which is especially attracting attention of the policymakers in the developing markets (Mintz-Woo et al, 2020). However, it is often observed that the burden of carbon taxation is relatively less in comparison to investment in eco-friendly designs and practices.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is often observed that the burden of carbon taxation is relatively less in comparison to investment in eco-friendly designs and practices. This severely impacts the sole objective of achieving carbon neutrality (Mintz-Woo et al, 2020). Hence, the taxation rules remain an important instrument, which decides whether organizations have sufficient incentive to move towards energy efficient practices.…”
Section: Introductionmentioning
confidence: 99%
“…Putting a price on fossil fuel extraction reduces the incentives of companies to explore and/or extract fossil fuel resources. Countries use a variety of approaches to tax fossil fuel production, including corporate profit taxes, rent taxes, income from resourceextracting state-owned enterprises or royalties (Elgouacem, 2020 [279]). The multitude of instruments makes it challenging to compare effective fossil fuel supply tax rates across countries.…”
Section: Figure 52 Carbon Contract For Differencesmentioning
confidence: 99%
“…As a result of the COVID-19 pandemic and economic shutdown, global energy demand and carbon emissions were expected to fall by 6% and 8%, respectively, by the end of April 2020 (IEA 2020). As the emission trading system (ETS), the critical tool to mitigate carbon emissions and combat climate change in the EU, regulates half of the EU's carbon emissions, its demand and prices should have plummeted during the COVID-19 pandemic (Mintz-Woo et al 2020;Sartzetakis 2021). However, the prices of EU carbon allowances (EUAs) have fallen less in 2020 than that in the 2008 financial crisis.…”
Section: Introductionmentioning
confidence: 99%